2010
DOI: 10.1038/mt.2009.263
|View full text |Cite
|
Sign up to set email alerts
|

Pretranscriptional Regulation of Tgf-β1 by PI Polyamide Prevents Scarring and Accelerates Wound Healing of the Cornea After Exposure to Alkali

Abstract: Corneal alkali burns are a serious clinical problem that often leads to permanent visual impairment. In this process, transforming growth factor (Tgf)-beta1 is upregulated and involved in the response to corneal injury and the process of corneal stromal scarring. To develop an efficient compound to inhibit Tgf-beta1 in the cornea, we designed GB1201, a pyrrole-imidazole (PI) polyamide targeting rat Tgf-beta1 gene promoter to the activator protein-1 (AP-1) binding site. GB1201 showed a high binding affinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…From paired heterocyclic amide building blocks of pyrrole and imidazole, PIPs can distinguish G/C and A/T (T/A) pairs via DNA minor groove binding with Im/Py and Py/Py pairs, respectively, down to the precision of a single hydrogen bond between the bases. Chemical functionalization provides versatility in regulating biological events [915] such as cell reprogramming, NF- κ B-dependent gene transcription, retinal development, and the inhibition of specific biological targets [16, 17]. Nevertheless, as PIPs principally bind typically well less than 20 bp, the impact of binding at genomic locations other than the intended design site remains unclear to-date.…”
Section: Introductionmentioning
confidence: 99%
“…From paired heterocyclic amide building blocks of pyrrole and imidazole, PIPs can distinguish G/C and A/T (T/A) pairs via DNA minor groove binding with Im/Py and Py/Py pairs, respectively, down to the precision of a single hydrogen bond between the bases. Chemical functionalization provides versatility in regulating biological events [915] such as cell reprogramming, NF- κ B-dependent gene transcription, retinal development, and the inhibition of specific biological targets [16, 17]. Nevertheless, as PIPs principally bind typically well less than 20 bp, the impact of binding at genomic locations other than the intended design site remains unclear to-date.…”
Section: Introductionmentioning
confidence: 99%
“…2; Table 1), including a pyrrole-imidazole polyamide drug that blocks transcription of the TGFB1 target gene (Yao et al 2009;Chen et al 2010;Matsuda et al 2011;Washio et al 2011;Igarashi et al 2015), antisense RNAs that target TGFB1 or TGFB2 mRNAs for degradation (Hau et al 2009;Vallieres 2009;Schlingensiepen et al 2011), antibodies against TGF-b ligands or receptors that block ligand -receptor engagement, and many small molecule ATP-mimetic TbRI kinase inhibitors (Fig. 2).…”
Section: Drugs That Block Tgf-b Signalingmentioning
confidence: 99%
“…We have already demonstrated that PI polyamide targeting TGF-β1 effectively attenuates progressive renal disease , stenosis of the carotid artery after angioplasty (Yao et al, 2009), alkali burn of the cornea (Chen et al, 2010), and hypertrophic scars (Washio et al, 2011). PI polyamides targeted to TGF-β1 may thus be a potent gene silencer at the transcription level.…”
Section: Discussionmentioning
confidence: 97%